2020
DOI: 10.1371/journal.pone.0239947
|View full text |Cite
|
Sign up to set email alerts
|

US primary care in 2029: A Delphi survey on the impact of machine learning

Abstract: Objective To solicit leading health informaticians' predictions about the impact of AI/ML on primary care in the US in 2029. Design A three-round online modified Delphi poll. Participants Twenty-nine leading health informaticians. Methods In September 2019, health informatics experts were selected by the research team, and invited to participate the Delphi poll. Participation in each round was anonymous, and panelists were given between 4-8 weeks to respond to each round. In Round 1 open-ended questions solici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Reflecting on these findings, the important question arises about whether teaching bodies and curricula should be adapted, not only for students but also for educators. In a recent survey, leading healthcare informaticians forecast that by 2029, AI/ML will incur workplace changes in primary care, with the need for increased training requirements in these fields (20). The present survey therefore raises questions about the preparedness of clinical psychology/psychotherapy students to fully engage in pressing debates about ethical and evidence-based issues pertaining to AI/ML tools, and in guiding patients on the use of psychotherapy and other mental health apps (21).…”
Section: Summary Of Major Findingsmentioning
confidence: 95%
“…Reflecting on these findings, the important question arises about whether teaching bodies and curricula should be adapted, not only for students but also for educators. In a recent survey, leading healthcare informaticians forecast that by 2029, AI/ML will incur workplace changes in primary care, with the need for increased training requirements in these fields (20). The present survey therefore raises questions about the preparedness of clinical psychology/psychotherapy students to fully engage in pressing debates about ethical and evidence-based issues pertaining to AI/ML tools, and in guiding patients on the use of psychotherapy and other mental health apps (21).…”
Section: Summary Of Major Findingsmentioning
confidence: 95%
“…Surveying general practitioners (GPs) directly, Blease et al 36 found that 94% of GPs believed that AI would be unable to replace GPs in roles requiring empathic ability, over any time scale, a perception shared with informaticians interviewed by the same team. 37 Along the same lines, Holford 38 and Powell 39 claimed that an integral part of the role of the doctor inevitably gets lost if the practice is translated into an algorithm. Using an anthropological perspective, Holford discussed this as the loss of deep knowledge, experience and intuition in relation to AI and technological progress.…”
Section: Open Accessmentioning
confidence: 99%
“…Leading figures in biomedical informatics advocate education in digital health for the healthcare workforce 1 2. In healthcare, artificial intelligence/machine learning (AI/ML)-enabled tools increasingly play a role by informing patient triage decisions, clinical decision support systems, and healthcare resource management3 – advances that are undoubtedly set to grow 4. Tens of thousands of healthcare apps are available for download by consumers, promising a range of services, from symptom tracking to diagnostic and treatment advice.…”
Section: Introductionmentioning
confidence: 99%